2009
DOI: 10.1080/00365510902829354
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume is elevated in patients with myocardial infarction with normal coronary arteries, as in patients with myocardial infarction with obstructive coronary artery disease

Abstract: Although the majority of cases of acute myocardial infarction are caused by atherosclerotic coronary artery disease (CAD), it can also occur in people with normal coronary arteries. One of the possible mechanisms causing myocardial infarction with normal coronary arteries (MINC) is transient occlusion of the infarct-related artery owing to platelet hyperactivity and thrombosis. Mean platelet volume (MPV), an indicator of platelet activation, has been shown to be elevated in patients with unstable angina and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…19,[21][22][23] In the present study also, MPV was statistically significantly increased in STEMI and UA compared to the controls, hence the current is in accordance with all above studies. Yaghoubi A et al 19 study showed that difference in MPV between MI patients and UA patients was not significant, like Khandekar et al in India.…”
Section: Discussionsupporting
confidence: 92%
“…19,[21][22][23] In the present study also, MPV was statistically significantly increased in STEMI and UA compared to the controls, hence the current is in accordance with all above studies. Yaghoubi A et al 19 study showed that difference in MPV between MI patients and UA patients was not significant, like Khandekar et al in India.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, MPV is higher in MI with normal coronary arteries compared to control subjects [16]. The important clinical implication of MPV is its predictive value of coronary angioplasty effectiveness.…”
Section: Discussionmentioning
confidence: 93%
“…28 In hypertensive patients, there is a compelling evidence on the role of platelet activation in hypertensive thrombotic complications including stroke 32 and myocardial infarction. 7 Increased platelet activation might be related to increased vascular thrombotic risk in prehypertension. However, in our study, increased MPV was negatively correlated with plasma total cholesterol, and low-density lipoprotein cholesterol was negatively correlated with minimal changes in absolute numbers.…”
Section: Discussionmentioning
confidence: 99%
“…6 MPV is an important biological variable that is drawing increased interest as an independent risk factor for myocardial infarction. 7 The literature on the association between MPV and stroke is inconsistent 8,9 and may also relate to the use of different methods to assess MPV and the variable time points used for MPV measurement after stroke onset. 10 Moreover, emerging evidence has shown that known cardiovascular risk factors, such as smoking, 11 diabetes mellitus, 12 obesity 13 and hypertension, 14,15 are associated with MPV.…”
Section: Introductionmentioning
confidence: 99%